Membangun Silabus Yang Kreatif : Menjawab Kebutuhan Belajar Secara Personal dan Fleksibel - Arliani Saputri; Indrian Satria; Julia Nofiani; Rania Zulfi Fajriyah (Yayasan Sagita Akademia Maju, 2025)
This article explores the development of a creative syllabus designed to address the growing need for personalized and flexible learning. In an educational landscape that increasingly values individual student needs and diverse learning styles, traditional, rigid syllabi often fall short. This paper argues for an innovative approach to syllabus construction that moves beyond static content delivery towards a dynamic framework. Key elements discussed include incorporating student choice, leveraging adaptive technologies, fostering interdisciplinary connections, and emphasizing project-based learning. The goal is to empower learners to take ownership of their educational journey, enabling them to pursue their interests, learn at their own pace, and engage with material in ways that are most meaningful to them. Ultimately, a creative syllabus aims to cultivate not just knowledge acquisition, but also critical thinking, problem-solving, and lifelong learning skills.